Development of a project-based e-module on Salacca sumatrana conservation to enhance students' creativity and ecoliteracy - Fitri Agustina Lubis; Iskandar Safri Hasibuan; Yetri Adela; Jalilah Azizah Lubis; Editha Dewi Purnamasari (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
This study aims to develop a project-based electronic module on the conservation of Salacca sumatrana, a local biodiversity resource in South Tapanuli. The ADDIE model development process was assessed for effectiveness using a quasi-experimental non-equivalent control group pre-test-post-test design. Participants consisted of 84 students from high schools in South Tapanuli. The research instruments included expert validation sheets, practicality questionnaires, TTCT-based creativity tests, and ecological literacy instruments measuring students' knowledge, attitudes, and skills. The expert validation results showed very good feasibility (98%). The teachers' practicality assessment reached 93.5%, categorizing the e-module as very practical. The effectiveness test results showed that the e-module had a moderate effect on creativity (Cohen's d = 0.45) and a large effect on ecological literacy, with a significant improvement in students' understanding of ecosystem threats (increasing from 58% to 96%) and biodiversity concepts (increasing from 60% to 82%) based on pre-test and post-test comparisons. A t-test revealed a statistically insignificant difference between the experimental and control groups for creativity (p = 0.080 > 0.05), though the moderate effect size (0.45) indicates practical educational impact. Practicality trials showed high student acceptance, with scores ranging from 82.20% to 92.69% across schools. These findings indicate that the project-based e-module is a feasible, practical, and effective learning resource for fostering students' creativity, ecological literacy, and ecological responsibility, as well as supporting local biodiversity conservation and promoting sustainable education.